Penerapan Tindakan Terapi Musik Pada Pasien Cedera Kepala Ringan Dengan Masalah Nyeri Akut Di Rumah Sakit Bhayangkara M. Hasan Palembang - Rifka Zalila; Rika Saputri; Nadya Ayu Pancawardhana (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Background: Data obtained from the Palembang city health office that the incidence of head injuries in 2018 there were (16.15) patients. Head injury (trauma capitis) is a mechanical injury that directly or indirectly affects the head that results in head wounds, fractures of the bones of the skull, tearing of brain membranes, and damage to brain tissue, as well as resulting in neurological disorders. One of the nonpharmacological therapies that can be given to patients who experience pain in minor head injuries is music therapy. Objectives: to gain real experience and knowledge and to document the application of music therapy to pain scales in nursing care for minor head injuries. Methods: this type of scientific paper uses a descriptive method with a case study approach to explore the problem of nursing care in two patients with minor head injuries. Nursing care was carried out on two patients, which was carried out on June 15 to 17, 2022. Results: from music therapy actions to Mr. A and Mr. D with the first diagnosis of acute pain related to physical injury agents. The results of the evaluation of the first patient, Mr. A, found that the patient experienced a decrease in the pain scale to 3 (mild), before music therapy the pain scale was 5 (moderate), the pain problem was resolved, and the intervention was stopped. For the evaluation, the second patient, Mr. D, obtained a pain scale of 2 (mild), before music therapy the pain scale was 4 (moderate), the pain problem was resolved, and the intervention was stopped. Conclusion: the results of the nursing evaluation on Mr. A and Mr. D problems resolved the intervention was stopped. It can be concluded that music therapy can reduce pain in patients with mild head injuries.